The Role of AI in Facilitating Positive Social Adaptation to Improve Adolescent Mental Well-Being - Akbar, Siti Gita Amalyah; Dinata, Konto Iskandar (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
This study aims to explore the role of artificial intelligence (AI) technology in facilitating social adaptation that positively impacts adolescents' mental well-being. In the digital age, AI has become an integral part of everyday life, especially among adolescents who are in a period of identity search and social exploration. This study used a descriptive quantitative approach with a survey method through a Likert scale-based questionnaire distributed online. Six main aspects were analyzed, namely AI's ability to facilitate social adaptation, generate self-confidence, impact on mental well-being, integration of psychological components, effectiveness in overcoming anxiety, and adolescents' level of trust in AI. Results showed that the AI was moderately effective in providing social and emotional adaptation support, with “positive impact on mental well-being” receiving the highest score (mean 3.83). However, adolescents' level of trust in the AI was low (mean 2.83), indicating the need for further development of a design approach that is more humanistic and sensitive to adolescents' psychosocial needs.